Reproducción de abejas (Apis mellífera) reinas utilizando cuatro tipos de traslarve. - Cepeda Soria, Ángel Danilo (2012)
In the sector of Pititig of the canton Bathrooms, county of Tungurahua, to an altitude of 1.830 m.s.n.m, temperature 21,50 °C and relative humidity 62,50. You study the reproduction of bees queens using four traslarve types. 5 beehives mothers were used with mestizo bees of two rises, to evaluate 4 treatments, with 4 repetitions for treatment and the size of the Experimental Unit was of 10 you surround realeras, using a total of 160 glasses. The study variables were: you surround accepted, you surround operculadas, birth and fecundation of bees queens. The reached results demonstrated with highly significant differences (P <0,01) the biggest percentages of real glasses accepted when using the concentration of it pulls real 80 and 100% with the 92,50 and 82,50%; the biggest percentage of glasses operculadas in 80 and 100% of real jelly with the 85,00 and 70,00%; the biggest percentage of bees born queens when using concentrations of the 80 and 100% of real jelly with the 75,0 and 55,0%; the biggest percentage of queens fecundated when using the 80 and 100% of jelly with the 75,00 and 52,50% and the biggest economic profitability’s in the concentrations of real jelly 80 and 100% with 1,36 and 1,58 of beneficial/cost. In consideration to the reached results, it is recommended in the central area of the country, to those producing of bees to use concentrations of the 80 and 100% encourages real in water bidestilada for the traslarve during the production of bees queens using the artificial method. Describers: you Surround realeras, traslarve, encourages real, cells operculadas, queens' fecundation, beneficio/costo.